Cost Optimization of Top Three Cloud Services Google, Azure and AWS using HybridCloud - et. al., Rupendra J. Chourasiya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The process of reducing your overall cloud spending by using your own available resources as add-onsfor the cloud infrastructure you are using for your business is Cloud cost optimization.This paper discusses the benefitsin terms of cost of applying distributed cloud computing technologies in the development of business. First, the conception of cloud computing is introduced, and then a hybrid cloud computing platform for business is designed.The distinguished characteristics of the proposed platform are then explained in detail, followed with the introductionto the new system of storage using remote hardware infrastructure and resources. An introduction to state-of-the-art products which can be used to build the proposed platform is given.